PENGUJIAN VALIDASI ANALISIS KADAR ANDROGRAFOLID SECARA KROMATOGRAFI CAIR KINERJA TINGGI (KCKT) DENGAN ELUASI GRADIEN TERHADAP EKSTRAK HERBA SAMBILOTO (ANDROGRAPHIS PANICULATA NESS) - Toetik Aryani (The East Java Biological Society, 2005)
Andrographolide of Andrographis paniculata Nees have been isolated and determined Extraction was carried out by maceration with ethanol as solvent. The concentration of Andrographolide was determined by HPLC method. The eluation was carried by out gradiently using methanol: water as an eluent and UV spectrophotometer at maks 228 as detector. The result of HPLC analysis are selectivity >1.2–1.5; r was 0.9937; precision was KV < 10%; accuracy > 90%; DL was 0.075; QL was 0.50 and PW < F table. Andrographolide content of Andrographis paniculata Nees from Banyuwangi was 6.25%, Kediri was 14.69% and Surabaya was 6.83%